Sorry but no sorry: The use and effects of apologies in airline webcare responses to NeWOM messages of flight passengers. (April 2021) - van Hooijdonk, Charlotte; Liebrecht, Christine
Abstract: Offering an apology is a strategy brands use in response to negative electronic word of mouth. However, its effectiveness is equivocal and may depend on its combination with other strategies. In this paper, the use and the effectiveness of offering an apology in webcare conversations between airlines and complaining customers on Twitter is investigated. In Study 1, a corpus study was conducted to examine whether and how apologies occurred in 480 webcare conversations. Offering an apology was the most frequently used response strategy. Moreover, accommodative strategies were more frequent than defensive strategies. In Study 2, we investigated the effectiveness of apologies separately and combined with a defensive and/or accommodative strategy. The experiment had a 2 (apology: present vs. absent) × 2 (defensive strategy: present vs. absent) × 2 (accommodative strategy: present vs. absent) between-subjects design. Flight passengers ( N = 151) assessed a webcare response to a service failure on the airline's reputation. Although the presence of an apology did not enhance brand reputation, a combination of both a defensive and accommodative strategy did. We conclude that airlines prefer an apology as response to online complaints, but the combination of defensive and accommodative strategies truly protects their reputation.